Fit4Life: A weight loss intervention for children who have survived childhood leukemia. Issue 5 (16th January 2014) - Huang, Jeannie S.; Dillon, Lindsay; Terrones, Laura; Schubert, Lynn; Roberts, William; Finklestein, Jerry; Swartz, Maria C.; Norman, Gregory J.; Patrick, Kevin
<x xml:space="preserve">Abstract</x> Background Children surviving acute lymphoblastic leukemia (ALL) are at increased risk for overweight and obesity over that of the general population. Whether a generic or tailored approach to weight management is needed for cancer survivors has yet to be tested. Procedure Thirty‐eight youth 8–18 years with BMI ≥ 85% who had survived ALL were recruited for a randomized clinical trial evaluating a weight management intervention (WMI) tailored for childhood ALL survivors (Fit4Life). Fit4Life recipients received a 4‐month web, phone, and text message‐delivered WMI tailored for cancer survivorship. Controls received a general WMI delivered via phone and mail. Assessments were performed at baseline and 4 months. Outcome data were analyzed according to assigned treatment condition over time. Results Most (80%, (70%, 100%) [median (IQR)]) of the assigned curriculum was received by Fit4Life participants as compared to 50% (40%, 65%) among controls. Fit4Life recipients ≥14 years demonstrated less weight gain (P = 0.05) and increased moderate‐to‐vigorous physical activity (P < 0.01) while all Fit4Life recipients reported reduced negative mood (P < 0.05) over time as compared to control counterparts. Conclusions We demonstrated acceptable feasibility of a WMI tailored for overweight and obese children surviving ALL utilizing a multimodal technology approach. Improved weight, weight‐related behavior, and psychological outcomes were demonstrated among Fit4Life intervention as compared to youth receiving a generic WMI. Data from this pilot trial may be used to design a larger trial to determine whether youth of all ages also can derive a benefit from a cancer survivor‐tailored WMI and whether short‐term outcomes translate into improved long‐term outcomes for childhood ALL survivors. Pediatr Blood Cancer 2014;61:894–900. © 2014 Wiley Periodicals, Inc.